Evaluation of lifestyle and nutritional status in off-site University Italian Students (ADISU-Foggia): A pilot study - Moscatelli, Fiorenzo; La Torre, Maria Ester; De Stefano, Maria Ida; Marinaccio, Luigi Antonio; Vasco, Paride; Marsala, Gabriella; De Maria, Antonella; Monda, Vincenzo; Villano, Ines; Limone, Pierpaolo; Monda, Marcellino; Messina, Antonietta; et al. (Progress in Nutrition, 2023)
Background and aim: Unhealthy lifestyle represent one of the main public problems. The World Health Organization (WHO) coined the term “globesity” in 2001 to emphasize the serious threat caused by the excessive weight gain of human beings around the world. The aim of this investigation is to carry out pilot study to detect the nutritional status, eating habits, lifestyle and psychological state related to eating disorders of the Apulian university population. Methods: In this study were recruited 80 students (54 female and 26 male; 21.2±2.16 years). Body composition, eating behaviors and physical activity levels were assessed. All participants completed questionnaires and then the nutritional visits. Results: Males have an average stature of 176.3 ± 8.2 cm and a weight of 73.6 kg ± 13.5. While the females have an average height of 162.2 cm ± 6.3 with a weight of 61.9 kg ± 15.2. The BMI on average is in the normal weight range for both males and females, respectively 23.7 ± 3.8 for males and 23.5 ± 4.6 for females. Males are more active than females. Eating habits shows that the participant consumed approximatively 50% of carbohydrates, 20 % of protein and 30% of lipids. Conclusions: These data shows that the diet of the sample analyzed is in line with national trends and with the departure from food models that have long been recognized as a fundamental for a correct lifestyle, also due to a choice of packaged foods that off-site students use a lot, confirming that nutrition educational program is fundamental, against obesity.